Evaluating VMAT Delivery Accuracy Using End-to-End Test for Different Types of VMAT Plans - Dameska, Angela; Teodosievska Dilindarski, Milena; Lukarski, Dushko (Sievert Association, 2023)
Volumetric modulated arc therapy (VMAT) is the next step in the improvement of the dynamic intensity modulated radiotherapy by improving the delivery efficiency and reducing the treatment time. In this study we have evaluated the delivery accuracy of different types of VMAT plans by performing an end-to-end test using the CIRS IMRT Thorax 002LFC phantom on two different radiotherapy units, a Varian iX Clinac and a Halcyon unit. We have created 10 different VMAT plans and measured the dose in different points according to a modified IAEA CRP E24017 protocol. For the measurement points representing the target volumes we have found that using two or three arcs gives acceptable results, but for single arc treatments the results were suboptimal. For low-dose regions, field size was found to have a more pronounced effect especially on the iX unit, with larger fields leading to slightly reduced accuracy. Inaccuracies are usually highest where the inhomogeneity of the body is greatest, such as the points representing the lungs and the spinal cord regions, where the computational algorithms themselves also contribute to the overall inaccuracy. In conclusion, the end-to-end test showed that the plans are clinically acceptable, but the recommendations for these particular machines would be not to use single arc treatments and to consider algorithm inaccuracies in regions of greater inhomogeneity during the treatment planning process.
Keywords: VMAT; End-to-end test; CIRS IMRT thorax phantom